PSYCHOLOGICAL FOUNDATIONS FOR DEVELOPING SPEED-STRENGTH QUALITIES AT THE STAGES OF SPORTS TRAINING IN 15–17-YEAR-OLD NATIONAL WRESTLING ATHLETES (Eureka Journal of Humanities and Social Research, 2026)
The article investigates the effectiveness of an adaptive-digital model in developing speed-strength qualities in 15–16-year-old national wrestling athletes. Training loads were tailored to the athletes’ individual physical and psychological characteristics and monitored in real time. Results showed significant improvements in speed, strength, endurance, and coordination, as well as increased motivation and concentration. The model is recommended for use in school wrestling clubs.
Keywords: national wrestling, speed-strength qualities, adaptive-digital model, individual approach, psychological preparation, physical preparation, motor skills, competition performance, coordination, motivation, muscle strength, plyometric exercises, training effectiveness, periodization